2018
DOI: 10.1001/jamapediatrics.2017.5211
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Levetiracetam vs Phenobarbital for Infantile Epilepsy

Abstract: IMPORTANCE More than half of infants with new-onset epilepsy have electroencephalographic and clinical features that do not conform to known electroclinical syndromes (ie, nonsyndromic epilepsy). Levetiracetam and phenobarbital are the most commonly prescribed medications for epilepsy in infants, but their comparative effectiveness is unknown. OBJECTIVE To compare the effectiveness of levetiracetam vs phenobarbital for nonsyndromic infantile epilepsy. DESIGN, SETTING, AND PARTICIPANTS The Early Life Epilepsy S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Hospitals may not currently have the necessary support for implementation and maintenance of regular expressions. 39,40 Steps to increase data utility for epilepsy research include (1) continued collaboration between institutions to share data for epilepsy research, 41,42 (2) building structured data elements into physician note templates to improve documentation at the point of care for later use in epilepsy research, (3) continued development of epilepsy-specific NLP tools to extract valuable information from unstructured clinical narratives in EMRs, [28][29][30][31]38 (4) increased adoption of standard epilepsy classification systems 43,44 to improve consistency of language used in EMRs, and (5) continued development of epilepsy-specific ontologies 45 and vocabularies 37 for epilepsy researchers using EMR data. We performed data analysis on a research server, after data were extracted from the EMR.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals may not currently have the necessary support for implementation and maintenance of regular expressions. 39,40 Steps to increase data utility for epilepsy research include (1) continued collaboration between institutions to share data for epilepsy research, 41,42 (2) building structured data elements into physician note templates to improve documentation at the point of care for later use in epilepsy research, (3) continued development of epilepsy-specific NLP tools to extract valuable information from unstructured clinical narratives in EMRs, [28][29][30][31]38 (4) increased adoption of standard epilepsy classification systems 43,44 to improve consistency of language used in EMRs, and (5) continued development of epilepsy-specific ontologies 45 and vocabularies 37 for epilepsy researchers using EMR data. We performed data analysis on a research server, after data were extracted from the EMR.…”
Section: Discussionmentioning
confidence: 99%
“…A higher proportion of infants in the phenobarbital group had developmental structural brain abnormalities. 30 Our study focuses on neonatal seizures in a population with brain injury and suggests no difference in treatment failure or neurodevelopmental outcomes for these infants.…”
Section: Discussionmentioning
confidence: 99%
“…7 A multicenter observational cohort study comparing the efficacy of levetiracetam and phenobarbital in infants with nonsyndromic epilepsy presenting between 1 month and 1 year of age found that levetiracetam was superior as initial monotherapy. 8 Shellhaas et al 9 enrolled newborns with seizures from seven United States Children's Hospitals. BFNC was found clinically in 11 of 611 neonates.…”
Section: Discussionmentioning
confidence: 99%